Characterization of Tomato yellow spot virus, a novel tomato-infecting begomovirus in Brazil - Calegario, Renata Faier; Ferreira, Sávio de Siqueira; Andrade, Eduardo Chumbinho de; Zerbini, Francisco Murilo (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was the biological and molecular characterization of a begomovirus detected in São Joaquim de Bicas, Minas Gerais, Brazil, named TGV-[Bi2], by determining its host range, complete nucleotide sequence and phylogenetic relationships with other begomoviruses. Biological characterization consisted of a host range study using either sap inoculation or particle bombardment as inoculation methods. The yellow spot virus can infect plants in Solanaceae and Amaranthaceae, including economically importat crops as sweet pepper, and weeds as Datura stramonium and Nicotiana silvestris. For the molecular characterization, the full-length genome (DNA-A and DNA-B) was amplified, cloned and completely sequenced. Sequence comparisons and phylogenetic analyses indicated that TGV-[Bi2] constitutes a novel begomovirus species named Tomato yellow spot virus (ToYSV), closely related to Sida mottle virus (SiMoV).